CZTSSe/Zn(O, S) heterojunction solar cells with 9.82% efficiency enabled via (NH4)2S treatment of absorber layer. (25th May 2021) - Jeong, Hiji; Nandi, Raju; Cho, Jae Yu; Pawar, Pravin S.; Lee, Hyo Seok; Neerugatti, KrishnaRao Eswar; Kim, Jin Hyeok; Heo, Jaeyeong
Abstract: The replacement of CdS buffer layer is desirable for the development of nontoxic, environmentally friendly kesterite thin‐film solar cells (TFSCs). Recently, several ternary compound semiconductors have been extensively investigated as an alternative buffer layer for Cd‐free TFSCs. Herein, the effectiveness of (NH4 )2 S treatment on the surface properties of the absorber, as well as the device performance of atomic layer deposited (ALD) Zn(O, S) buffer‐based CZTSSe solar cells, has been investigated. X‐ray photoelectron spectroscopy (XPS) results showed that the elemental compositions of CZTSSe surface were significantly influenced by (NH4 )2 S treatment, whereas the surface morphologies of the CZTSSe‐absorber layers remained unaffected. The XPS results further suggested that the (NH4 )2 S solution treatment substantially removed the native oxide layer from the CTZSSe absorber surface. The fabricated CZTSSe/Zn(O, S) device without (NH4 )2 S treatment displayed an initial cell efficiency of 7.46%. The energy conversion efficiency increased significantly to 9.82% after the (NH4 )2 S treatment of absorber layers for an optimum duration of 1 min; to the best of our knowledge, this is the highest efficiency achieved to date for Zn(O, S) buffer‐based kesterite solar cells. The improved device performance is predominantly attributed to the pronounced increase in the fill factor (FF) of TFSCs resulting from the removal of oxides/hydroxides from the CZTSSe surface and passivation of absorber surface with sulfur species. However, increasing the treatment duration to 3 or 5 min resulted in the deterioration of cell efficiency, primarily due to the progressive degradation in the FF of the device. This study demonstrates a plausible route to improve the performance of Zn(O, S) buffer layer‐based kesterite solar cells through a simple surface treatment of the absorber layers using (NH4 )2 S solution. Abstract : A power conversion efficiency of 9.82% is achieved for atomic layer deposited Zn(O, S) buffer layer‐based CZTSSe solar cells through a simple surface treatment of the absorber layers using (NH4 )2 S solution.